Developing Tourism Attractions Through Ethnic Marketing: Case Study of the Semarang Old Town Festival - Hermawan, Daniel (Komunitas: International Journal of Indonesian Society and Culture, 2024)
Semarang is renowned for its multiculturalism, with a diverse population of Javanese, Chinese, Arab, Indian, and other ethnic groups. This fosters the assimilation of the culture and indigenous knowledge of Semarang, which is abundant in cultural heterogeneity. The Semarang Old Town Festival was launched by the Oen Semarang Foundation (OSF) and subsequently expanded by the Semarang City Government as a recurring annual event. This festival encompasses a diverse range of artistic and cultural communities. This study aims to investigate the ethnic marketing strategies employed by the organizers of the Semarang Old Town Festival to develop tourism attractions. This study employs a qualitative methodology, utilizing a case study technique, to investigate the perspectives of managers and observe the execution of the 2023 Semarang Old Town Festival in enhancing tourism attractions through ethnic marketing, which is owned by the residents of Semarang City. The process of organizing the Semarang Old Town Festival revealed city branding, collaboration, and community empowerment as the primary themes.